Respiratory Syncytial Virus's Non-structural Proteins: Masters of Interference - Thornhill, Elena Margaret; Verhoeven, David (Frontiers in Cellular and Infection Microbiology, 2020)
Respiratory Syncytial Virus (RSV) is a highly prevalent virus that affects the majority of the population. The virus can cause severe disease in vulnerable populations leading to high hospitalization rates from bronchiolitis or secondary bacterial infections like pneumonia. Two early proteins, non-structural proteins (Ns1 and Ns2), strongly over-ride the antiviral innate system but also diminish the adaptive response as well. This review will cover interactions of Ns1 and Ns2 with the host antiviral response with a focus on alterations to signaling pathways, nuclear cytokine transcription, and mitochondrial manipulations.